Ответ:
5
Пошаговое объяснение:
1) [tex]\frac{2cb}{c^{2}-b^{2}} + \frac{c-b}{2c+2b}=\frac{2cb}{(c-b)(c+b)} + \frac{c-b}{2(c+b)}=\frac{4cb+(c-b)^2}{2(c+b)(c-b)}=\frac{c^2+2cb+b^2}{2(c+b)(c-b)}=\frac{(c+b)^2}{2(c+b)(c-b)}=\frac{(c+b)}{2(c-b)}[/tex]
2)[tex]\frac{(c+b)}{2(c-b)} * \frac{10c}{c+b} + \frac{5b}{b-c} = \frac{5c}{c-b}+\frac{5b}{b-c}=\frac{5b}{b-c}- \frac{5c}{b-c}= \frac{5(b-c)}{b-c}=5[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
5
Пошаговое объяснение:
1) [tex]\frac{2cb}{c^{2}-b^{2}} + \frac{c-b}{2c+2b}=\frac{2cb}{(c-b)(c+b)} + \frac{c-b}{2(c+b)}=\frac{4cb+(c-b)^2}{2(c+b)(c-b)}=\frac{c^2+2cb+b^2}{2(c+b)(c-b)}=\frac{(c+b)^2}{2(c+b)(c-b)}=\frac{(c+b)}{2(c-b)}[/tex]
2)[tex]\frac{(c+b)}{2(c-b)} * \frac{10c}{c+b} + \frac{5b}{b-c} = \frac{5c}{c-b}+\frac{5b}{b-c}=\frac{5b}{b-c}- \frac{5c}{b-c}= \frac{5(b-c)}{b-c}=5[/tex]